2021
DOI: 10.3390/app11093766
|View full text |Cite
|
Sign up to set email alerts
|

Low-Calorie Beverages Made from Medicinal Plants, Flowers and Fruits: Characteristics and Liking of a Population with Overweight and Obesity

Abstract: Nowadays, there are few options of low or no added sugar drinks offering health benefits and oriented to consumers with a special health condition, such as overweight and obesity. The objective of this work was to develop and characterize a low-calorie antioxidant beverage made from aqueous extracts of medicinal plants (Melissa and lemon verbena), flowers (chamomile and bougainvillea), and fruits (guava, pineapple, strawberry, orange, and tangerine) as an alternative for people with overweight and obesity. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Contreras‐López et al. ( 2021 ) reported the same trend of effect of herbal extract addition in beverage 6.85–4.55 when supplementation of chamomile herbal extract increased from 0% to 10%.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Contreras‐López et al. ( 2021 ) reported the same trend of effect of herbal extract addition in beverage 6.85–4.55 when supplementation of chamomile herbal extract increased from 0% to 10%.…”
Section: Resultsmentioning
confidence: 73%
“…Hence, an increase quantity of chamomile herbal extract affected the overall appearance of the beverage. -López et al (2021) reported the same trend of effect of herbal extract addition in beverage 6.85-4.55 when supplementation of chamomile herbal extract increased from 0% to 10%.…”
Section: Appearancementioning
confidence: 59%